Gerechtigkeit aus der Ferne? Herausforderungen der nationalen Verfolgung von Völkerrechtsverbrechen - Keul, Katja (Beiträge zum Internationalen und Europäischen Strafrecht / Studies in International and European Criminal Law and Procedure (IES), 2023)
»Distant Justice? Challenges in The National Prosecution of International Crimes«: What challenges does the decentral enforcement of international criminal law pose for national justice systems and how can these be overcome? The anthology »Distant Justice?« brings together scholars from various disciplines and representatives from all areas of judicial practice in order to discuss the particularities of national core crimes proceedings and to lay the foundation for an empirically and scientifically sound further development of national international criminal procedure law.